Consumer Legal Protection Against 'Oto' Public Transport Practices in Ambon City: A Case Study of Premature Passenger Drop-off Before Destination - Tantaru, Fernando (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: This article analyzes the legal issues surrounding the practice of prematurely dropping off passengers in the “oto” public transportation service in Ambon City. The issue has raised public concern due to its impact on passenger rights and comfort, as well as the obligation of drivers to provide agreed-upon services.Purposes of the Research: The purpose of this study is to examine the legal protection afforded to passengers under Indonesian law, particularly in relation to unfair transportation practices and violations of consumer rights by “oto” drivers.Methods of the Research: This research uses a normative legal method, employing statutory and conceptual approaches. It focuses on analyzing relevant laws such as Law Number 22 of 2009 on Traffic and Road Transport and Law Number 8 of 1999 on Consumer Protection to determine the obligations of public transport providers.Findings of the Research: The findings show that prematurely dropping off passengers without justification constitutes a breach of both transportation and consumer protection laws. This study contributes to the discourse by highlighting the need for improved legal enforcement and increasing public awareness regarding consumer rights in the public transportation sector, particularly in underserved urban areas like Ambon.